Local and Global Weak Solutions for Elliptic Nonlinear Equations (European Journal of Pure and Applied Mathematics, 2025)
In this work, it is considered that a certain quasilinear elliptic equation in an open bounded domain in Rn over a vector space, and we derive gradient estimates for weak solutions of p-Laplacian type elliptic equations with tiny bounded mean oscillation coefficients locally Lp, p ≥ q. In addition, we provide the key findings.
Keywords: weak solution, Nonlinear equation, measurable coefficients, gradient estimates, Holder’s inequality.